THE ESTABLISHMENT OF A NATIONAL PRESS IN THE COUNTRY OF TURKESTAN DURING THE RULE OF CHERISH RUSSIA (Scientific journal of the Fergana State University, 2024)
In this article, an attempt was made to briefly cover the emergence of national publications in Turkestan under the rule of Tsarist Russia in the beginning of the 20th century, the reasons for the creation of newspapers and magazines, the contributions of modern intellectuals to the national press, the topics covered in them, and how their fate ended.